Attentional M100 gain modulation localizes to auditory sensory cortex and is deficient in first‐episode psychosis. Issue 1 (8th September 2022) - Curtis, Mark T.; Ren, Xi; Coffman, Brian A.; Salisbury, Dean F.
Abstract: Selective attention is impaired in first‐episode psychosis (FEP). Selective attention effects can be detected during auditory tasks as increased sensory activity. We previously reported electroencephalography scalp‐measured N100 enhancement is reduced in FEP. Here, we localized magnetoencephalography (MEG) M100 source activity within the auditory cortex, making novel use of the Human Connectome Project multimodal parcellation (HCP‐MMP) to identify precise auditory cortical areas involved in attention modulation and its impairment in FEP. MEG was recorded from 27 FEP and 31 matched healthy controls (HC) while individuals either ignored frequent standard and rare oddball tones while watching a silent movie or attended tones by pressing a button to oddballs. Because M100 arises mainly in the auditory cortices, MEG activity during the M100 interval was projected to the auditory sensory cortices defined by the HCP‐MMP (A1, lateral belt, and parabelt parcels). FEP had less auditory sensory cortex M100 activity in both conditions. In addition, there was a significant interaction between group and attention. HC enhanced source activity with attention, but FEP did not. These results demonstrate deficits in both sensory processing and attentional modulation of the M100 in FEP. Novel use of the HCP‐MMP revealed the precise cortical areas underlying attention modulation of auditory sensory activity in healthy individuals and impairments in FEP. The sensory reduction and attention modulation impairment indicate local and systems‐level pathophysiology proximal to disease onset that may be critical for etiology. Further, M100 and N100 enhancement may serve as outcome variables for targeted intervention to improve attention in early psychosis. Abstract : The use of magnetoencephalography and the Human Connectome Project multimodal parcellation revealed precise cortical areas underlying attention modulation of auditory sensory activity in healthy individuals and impairments in early psychosis. The sensory reduction and attention modulation impairment indicate pathophysiology proximal to disease onset that may be critical for etiology.